Metabolic Syndrome in the Middle Age: Insights from the Hemoglobin Glycation Index - Lita, Tanjida Ruba; Begum, Ifat Ara; Rahman Apourba, Md Khalid Bin (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Metabolic syndrome (MetS) is a global health issue linked to obesity, hypertension, dyslipidemia, and insulin resistance, increasing the risk of type 2 diabetes and cardiovascular diseases. In Bangladesh, MetS prevalence is high, especially among middle-aged individuals. The hemoglobin glycation index (HGI) has emerged as a potential marker for glycemic control, offering insights beyond traditional HbA1c by accounting for individual variations in glucose metabolism. However, its association with MetS remains underexplored. Objective: To investigate the relationship between HGI and MetS components, as well as assess HGI’s potential as a metabolic risk biomarker. Methods: This cross-sectional study was conducted at the Department of Biochemistry, Sir Salimullah Medical College, Dhaka, Bangladesh, between March 2023 and February 2024. A total of 200 purposively selected middle-aged residents of old region of Dhaka city, Bangladesh, were enrolled. Data on demographics, medical history, physical examination, and lab findings were collected and analyzed. Results: Among 200 participants (46.5% male, 53.5% female), MetS prevalence was 27.5%, higher in the high HGI group (50.5%) than the low HGI group (5%). High HGI was significantly associated with waist circumference, systolic blood pressure, and triglycerides (p<0.05), while HDL was lower. Logistic regression showed a higher MetS risk in the high HGI group (OR= 17.878, 95% Cl: 6.119 52.232), as linking high HGI to abdominal obesity, hypertension, hypertriglyceridemia, and MetS (p<0.05). Conclusion: High HGI may serve as an independent marker of MetS, identifying individuals at higher risk, though large-scale studies are needed for validation. International Journal of Human and Health Sciences Vol. 09 No. 02 Apr’25 Page: 119-124